Ideologi Konstitusi Piagam Madinah dan Relevansinya dengan Ideologi Pancasila - Nurhadi Nurhadi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
The Medina Charter as the first constitutional document in Islam, has relationship with Pancasila in the Jakarta Charter as religious ideology. It shows that the Medina Charter has relevance to the philosophical values of Pancasila as the ideology of the Indonesia. This paper presents the relationship between the Medina Charter abbd Pancasia from normative and philosophical point of view in order to prove that the Constitution's Ideology of the Medina Charter is very relevant to the Jakarta Charter with the Philosophical values of Pancasila. The first principle (or Sila) of Pancasila Belief in one supreme being is in line with article in the Medina Charter about monotheism and aqedah. The second Sila of Pncasila Just and Civilized Humanitarism is in relation with the Articles about Human Rights in the Medina Charter. The third Sila of Pancasila about the comitment to the unity of Indonesia is also stated in Articles of Medina Charter about unity and brotherhood. The forth principle about the idea of people led or governed by wise politics in line with the Articles about deliberation and agreement. The last principle about the commitment to Social Justice for All Indonesian People is similar with the law of human rights in the Medina Charter.